2007
DOI: 10.1007/s10578-007-0087-0
|View full text |Cite
|
Sign up to set email alerts
|

Objective Versus Subjective Assessment of Methylphenidate Response

Abstract: Subjective improvement-assessment in attention deficit/hyperactivity disorder (ADHD), following a single dose of methylphenidate (MPH) was compared to performance on the Test-of-Variables-of-Attention (TOVA). Self-perception was assessed with the clinical-global-impression-of-change (CGI-C). Participants included 165 ADHD subjects (M:F ratio 67%:33%) aged 5-18 (11.09 +/- 3.43) years. TOVA was administered before and after MPH challenge (0.3 mg/kg). Self-perception CGI-C scores were compared to the TOVA scores.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…14 Several studies, using the Test of Variables of Attention (TOVA ® ), which combines a CPT with minimal language demands and no left-right discrimination, 15 showed improvement in commission scores, response time, and ADHD scores, while significant improvements regarding the omission variable were found in two of three studies. [16][17][18] In preschoolers, the opposite results were obtained with significant improvement in omission, response time score and response time variability score, but not in the commission score, following a single dose of MPH. 19 Studies using advanced CPT versions, including motion analysis, provide additional evidence.…”
Section: Introductionmentioning
confidence: 96%
“…14 Several studies, using the Test of Variables of Attention (TOVA ® ), which combines a CPT with minimal language demands and no left-right discrimination, 15 showed improvement in commission scores, response time, and ADHD scores, while significant improvements regarding the omission variable were found in two of three studies. [16][17][18] In preschoolers, the opposite results were obtained with significant improvement in omission, response time score and response time variability score, but not in the commission score, following a single dose of MPH. 19 Studies using advanced CPT versions, including motion analysis, provide additional evidence.…”
Section: Introductionmentioning
confidence: 96%
“…In previous studies comparing subjective ADHD symptom rating scales, with scores obtained using an objective neuropsychological test for the assessment of hyperactivity, inattention, and impulsivity, it was found that agreement between these two measurements was not as strong as anticipated (Manor et al 2008;Sumner et al 2010). These results prompted us to find potential predictors associated with differences between subjective perceptions and objective measurements in children with ADHD treated with MPH.…”
Section: Introductionmentioning
confidence: 98%
“…Although the prevalence of ADHD is thought to decrease with age; these estimates suggest that ADHD is one of the most common adult psychiatric disorders. Moreover, the true population prevalence of the disorder is likely to be higher since under-reporting of symptom severity is common and because of problems with current diagnostic methods applied to adults [2], [23], [24].…”
Section: Introductionmentioning
confidence: 99%